EFEKTIVITAS KONSENTRASI PUPUK CAIR TNF DAN DOSIS LIMBAH BUNGA KENANGA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea Mays Saccharata Sturt) VARIETAS TALENTA - Pamuji Setyo Utomo; Samsul Ma'arif; Aulia Dewi Rosanti (Jurnal Ilmiah Hijau Cendekia, 2022)
The sweet corn plant is a commodity crop and belongs to the family of grasses, the genus Zea and the species of Zea Mays Saccharata. Fertilization of sweet corn serves to increase levels of sweetness, production and growth of sweet corn. One of the nutrients needed by plants is organic matter. The function of organic matter is to improve or increase soil fertility so that crop production is increased. One form of organic material used in this study is compost made from the remnants of essential oil refining waste or called cananga flower waste. This study aims to determine the interaction between the concentration of liquid fertilizer TNF (Trace Nutrient Fertilizer) and cananga flower doses on the growth and production of sweet corn (Zea Mays Saccharata Sturt) Talenta varieties. The experiment used a 2 factor randomized block design with 9 levels of treatment and 3 replications. The composition of the treatment is P1 (TNF liquid fertilizer 5 ml / l), P2 (TNF liquid fertilizer 10 ml / l), P3 (TNF liquid fertilizer 15ml / l) while the second factor is L1 (5 tonnes / ha cannary waste flower) , L2 (Canaan flower waste 10 tons / ha) L3 (Cananga flower waste 15 tons / ha). The use of TNF liquid fertilizer, cananga flower waste or a combination of both produces high growth. The combination of both can increase vegetative and generative growth of sweet corn plants. The combination of the treatment of the two factors occurs in the interaction variables observed height, stem diameter and sweetness level. There was a real effect of single factor P (TNF liquid fertilizer) on plant height variable, variable weight of cob with cob and variable weight of cob without cob. Of the two factors obtained the best results with a combination of P3L3 treatment